Research progress of endogenous hematoma absorption after intracerebral hemorrhage - Fu, Peijie; Zhang, Manqing; Wu, Moxin; Zhou, Weixin; Yin, Xiaoping; Chen, Zhiying; Dan, Chuanjun (Frontiers in Neurology, 2023)
Non-traumatic intraparenchymal brain hemorrhage is referred to as intracerebral hemorrhage (ICH). Although ICH is associated with a high rate of disability and case fatality, active intervention can significantly lower the rate of severe disability. Studies have shown that the speed of hematoma clearance after ICH determines the patient's prognosis. Following ICH, depending on the hematoma volume and mass effect, either surgical- or medication-only conservative treatment is chosen. The goal of promoting endogenous hematoma absorption is more relevant because surgery is only appropriate for a small percentage of patients, and open surgery can cause additional trauma to patients. The primary method of removing hematoma after ICH in the future will involve understanding how to produce and manage macrophage/microglial endogenous phagocytic hematomas. Therefore, it is necessary to elucidate the regulatory mechanisms and key targets for clinical purposes.